Identification and strategies for triple-negative breast cancer subtypes - Rokhim Suryadi; Bambang Supriyo; Reza Mawardy (Institute of Computer Science (IOCS), 2023)
Triple-Negative Breast Cancer (TNBC) is a subtype of Breast Cancer (BC) with high mortality, early recurrence, more frequent, poor prognosis, and comparative data have shown that women with the TNBC phenotype have a 5-year overall 19 % survival lower and 18% lower disease-free survival than non-TNBC counterparts. The purpose of this study is to find out some of the identification and strategic management of Triple Negative Breast Cancer (TNBC). This research method used descriptive qualitative through the Systematic Literature Review (SLR) approach. The identifications obtained seven TNBC subtypes categorized and labeled differently such as Basal-Like 1 (BL1), Basal-Like 2 (BL2), Immunomodulatory (IM), Mesenchymal (M), Mesenchymal Stem–Like (MSL), Luminal Androgen Receptor (LAR), and Unstable (UNS). The strategy used the Development of a Breast Cancer Prediction Model with PPI Data and Support Vector Machines, Robust Identification of Target Genes and Outliers in TNBC data, and Sensitivity of Cell Lines to Heat Shock Protein 90 Inhibitor (Hsp90i). Based on the several strategies that have been described, there are various kinds of tests to determine TNBC according to the needs of each test. However, there is still no optimal solution that is suitable for all conditions.